How the reading habit affects the writing proficiency of the students from Composition I courses during semester II, 2016 at the Foreign Languages Department of the University of El Salvador - Orellana Pineda, Elizabeth; Alfaro Rodríguez, Antonio Josué; Elías Granados, Reynaldo Daniel (2024)
The research project was focused on the explanation of how The Reading Habit Affects The Writing Proficiency of the students from composition I courses during the semester II, 2016 at the Foreign Languages Department of the University of El Salvador. The purpose of this research project was to verify if the students had the reading habit and how this influenced on their writing performance.